On Passivity-Shortage of Human Operators for A Class of Semi-autonomous Robotic Swarms. Issue 34 (2019) - Surya Atman, Made Widhi; Noda, Kosei; Funada, Riku; Yamauchi, Junya; Hatanaka, Takeshi; Fujita, Masayuki
Abstract: This paper analyzes perceived workload and passivity-shortage of human operators for a class of semi-autonomous robotic swarms. First, we briefly introduce the passivity-short-based architecture presented in one of our previous works, which guarantees human-enabled motion synchronization to desired position/velocity references under the assumption that the human operator's thought process is a passivity-short system. It is observed that changes in parameter affects the visual feedback to the operator and also the complexity of the setups. Through user-studies using a human-in-the-loop simulator and questionnaires, we observe an increase in the perceived workload of the human operator for more complex setups. The result imposes the trade-off for less workload vs. clarity of the robotic swarms' information to the human operator. Furthermore, through non-parametric system identification on data from user-studies, it is observed that all obtained models of the participants have the passivity-short property.